《送你一朵小红花》影片中的修辞手法分析 PENGGUNAAN GAYA BAHASA PADA FILM “A LITTLE RED FLOWER” - Alwiyah Rahmatika; Jocelyn Johan (Journal of Language, Literature and Teaching, 2022)
Rhetoric is a way of expressing ideas through language, using language effectively. This paper takes